2013
DOI: 10.5430/jnep.v4n3p124
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Resuscitation team roles: What constitutes a team and who’s looking after the family?

Abstract: Aim of study: This study aimed to investigate the attitudes of personnel working in emergency departments on the constitution of a resuscitation team in particular the perceptions of the family liaison role. Methods:A paper base survey on family presence during resuscitation was distributed to emergency personnel working in 18 public departments in the state of Victoria, Australia.Results: A combination of nurses (n = 282) and doctors (n = 65) working in rural and metropolitan emergency departments, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Furthermore they reported that 55% of the physicians in the CPR team had a specialist qualification [21]. A survey conducted in the UK, reported the team leader is in 73-82% of cases represented by an emergency consultant [23]. In the present study we found comparable results: in the roles of team leader, airway manager and circulation manager the participation of residents and medical specialist was almost equally distributed.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore they reported that 55% of the physicians in the CPR team had a specialist qualification [21]. A survey conducted in the UK, reported the team leader is in 73-82% of cases represented by an emergency consultant [23]. In the present study we found comparable results: in the roles of team leader, airway manager and circulation manager the participation of residents and medical specialist was almost equally distributed.…”
Section: Discussionsupporting
confidence: 69%
“…Existing literature around FPDR is still inconclusive as to the team's position and actual practice in application. Although various policies have been written around family presence at these events, based on the benefits for both the family and the patient [10,16], in many cases there is still ambiguity around implementing them and confusion still exists among the resuscitation team members [20,21]. Emergency personnel in one phenomenological study, noted that a number of perceived barriers still exist, including fear and concern about exposure of professional practice and decision making [21].…”
Section: Introductionmentioning
confidence: 96%
“…A separate care coordinator role, who is assigned to care for the family and not take part in the resuscitation has been well documented as essential to the successful implementation of FPDR [7,16]. The care coordinator is responsible for assessing the family's appropriateness, based on coping, co-operative behaviours and perceived emotional readiness to be present in the resuscitation room while providing comfort measures and addressing any ongoing concerns [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resuscitation, non-technical skills, human factors, leadership, work ED staff suggest that, during resuscitative care episodes, roles and responsibilities form a hierarchy (Porter et al 2014), which is reflected in resuscitation team assessment. This suggests that team dynamics are informed by individuals' perceptions of their roles (McKay et al 2012).…”
Section: Introductionmentioning
confidence: 99%